IEEE International Conference on Computer Systems and Applications, 2006. 2006
DOI: 10.1109/aiccsa.2006.205229
|View full text |Cite
|
Sign up to set email alerts
|

FuFaIR: a Fuzzy Farsi Information Retrieval System

Abstract: Persian (Farsi) is one of the languages of Middle East. There are significant amount of Persian documents available in digital form and even more are created every day. Therefore, there is a necessity to implement Information Retrieval System with high precision for this language. This paper discusses the design, implementation and testing of a Fuzzy retrieval system for Persian called FuFaIR. This system also supports Fuzzy quantifiers in its query language. Tests have been conducted using a standard Persian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 11 publications
0
17
0
2
Order By: Relevance
“…Fuzzy logic [19], VSM [20] and language modeling methods [21]were used in the studies done about the retrieval of Persian documents. Persian test collection is introduced in [7] where authors used a number of documents in law domain.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Fuzzy logic [19], VSM [20] and language modeling methods [21]were used in the studies done about the retrieval of Persian documents. Persian test collection is introduced in [7] where authors used a number of documents in law domain.…”
Section: Related Workmentioning
confidence: 99%
“…Also experiments in [21] suggest the usefulness of language modeling techniques for Persian. Oroumchian et al [20] used N-gram method in search for Persian documents and they give better results by applying LCA (Local Context Analyses) and N-Grams. Considering trigrams and 4-grams extracted from documents and not using stemming process they showed that compared with VSM, 4-gram method increases retrieval efficiency for searching.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [10] proposed the design and testing of a Fuzzy retrieval system for Persian (FuFaIR) with support of Fuzzy quantifiers in its query language and their experiments showed that the retrieval system outperforms the vector space model. Also experiments in [2] Furthermore, Compression of Persian text for web was assessed on Hamshahri collection in [12] in which the authors could obtain up to 52% reduction in size.…”
Section: Related Work On Persianmentioning
confidence: 99%
“…Where w m,n is calculated using equation (10). Then Combinatorial Translation Probability (CTP) is a |T(q 1 )|×|T(q M )| matrix that is calculated by multiplication of all of the W k matrices:…”
Section: Combinatorial Translation Probabilitymentioning
confidence: 99%